Quality indicators for care of cancer patients in their last days of life: Literature update and experts' evaluation - Raijmakers, Natasja; Galushko, Maren; Domeisen, Franzisca; Beccaro, Monica; Lundh Hagelin, Carina; Lindqvist, Olav; Popa-Velea, Ovidiu; Romotzky, Vanessa; Schuler, Stefanie; Ellershaw, John; Ostgathe, Christoph (Journal of Palliative Medicine, 2012)
Background: Quality indicators (QIs) are needed to monitor and to improve palliative care. Care of patients in the last days of life is a discrete phase of palliative care and therefore specific QIs are needed. This study aimed to identify and evaluate current QIs against which to measure future care of patients in the last days of life. Methods: To identify QIs for patients in the last days of life an update of the literature and national guidelines was conducted. Subsequently, an international panel of palliative care experts was asked to evaluate the identified QIs: how well they describe care and how applicable they are for care in the last days of life. Also additional QIs were asked. Results: In total, 34 QIs for care in the last days were identified in the literature and guidelines. The experts (response rate 58%) agreed with seven QIs as being good descriptors and applicable: concerning a home visit for the family following a patient's death, the presence of a dedicated family room, limited patients receiving chemotherapy, limited need for pain control, gastrointestinal symptoms, and communication from professional to patient and family. The experts also suggested 18 additional topics for QIs for the last days of life. Conclusion: Currently no definite set of QIs exist to describe quality of care of patients in their last days of life. New QIs that are focused on care for patients in their last days of life, their relatives, as well as their professional caregivers are needed. © Copyright 2012, Mary Ann Liebert, Inc. 2012.
CRIS-Team Scopus Importer:2025-10-27